Soft X-Ray Polarimeter: Potential Instrumentation and Observations - Herman L. Marshall; Norbert S. Schulz (Acta Polytechnica CTU Proceedings)
We present an instrument design capable of measuring linear X-ray polarization over a broad-band using conventional spectroscopic optics. A set of multilayer-coated flats reflects the dispersed X-rays to the instrument detectors. The intensity variation with position angle is measured to determine three Stokes parameters: I, Q, and U - all as a function of energy. By laterally grading the multilayer optics and matching the dispersion of the gratings, one may take advantage of high multilayer reflectivities and achieve modulation factors >90% over the entire 0.2 to 0.8 keV band. This instrument could be used in a small suborbital mission or adapted for use in an orbiting satellite to complement measurements at high energies. We present progress on laboratory work to demonstrate the capabilities of key components.